Malaysian Gen Y employees’ work expectations and its influence on engagement - Ch’ng, Lay Im (2018)
Generation Y (Gen Y), the youngest and fastest growing generation in today’s workforce, is flooding into the workforce and will make up 50% of the workforce population globally. They have radically different traits, high workplace expectations and demands in comparison with previous generations. They are less loyal and quick to leave their organizations if their expectations are not met. Managing, retaining and engaging today’s generation of young workers are challenging. Gallup 2016 research in the US reported that Gen Y are the least engaged generation with only 29% of Gen Y are engaged at work, with the remaining 71% either not engaged or actively disengaged. An engaged workforce can drive profitability, productivity and improve retention for businesses. Organizations that have the ability to proactively address the new generation’s expectations for work in turn not only increase engagement levels but also ensure sustainable business profitability. The purpose of this study is to examine the influence of work expectations on engagement among Malaysian Gen Y employees. The study will provide a clear insight of the work expectations of Gen Y employees and help organizations gain a better understanding on how to further engage with this young generation. This study used a triangulation methodology, i.e., self-administrated questionnaire using 5-point Likert scale and semi-structured interviews with four human resources specialist from different industries. Primary data was collected from 134 Malaysian Gen Y respondents who are currently working. The results indicated all four independent variables, i.e., employee-manager relationship, pay and benefits, work environment and career development have a strong positive relationship with engagement. Work experience showed the strongest positive relationship and employee-manager relationship the weakest. Three recommendations were presented and suggested for business leaders and human resources practitioners with the aim of enhancing engagement with this young generation. Among others, companies can drive productivity and engagement with workplace gamification. Furthermore, organizations should initiate flexible friendly workplace by providing more choices and options on flexible work arrangements (FWA), pay and benefits to employees. Companies are also recommended to focus on cultivating transformational leadership behaviour in managers where transformational leaders create a supportive environment where responsibility is shared, motivate staff to maximize potential, trust and provide autonomy to team members.